1991
DOI: 10.1029/91ja00793
|View full text |Cite
|
Sign up to set email alerts
|

Estimating radiated power from a conducting tethered satellite system

Abstract: In anticipation of the upcoming TSS‐1 experiment, theoretical calculations are made of radiated power from a conducting tethered satellite system. The radiation results from the steady motion of the system through the ionospheric plasma and it is stimulated by collection and emission of charge by the noninsulated surfaces of the tethered end connectors. A model of the current system is developed which incorporates the tether wire, satellite surfaces, and sheath currents. The radiation impedance of the current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…For dense beams a virtual systems generated in the ambient plasma as a result of large cathode will form in the beam at a point where the beam orbiting structures and large plas•na clouds have therefore electrons stagnate as their velocity away from the spacecraft much in common. The radiation from large space strucis reduced, due to the electrostatic forces in the beam and tures have been studied by Donohue et al [1991], current the spacecraft, which charges to positive potentials [ Winglee closure and radiation for large clouds have been treated anand Pritchett, 1988;Pritchett, 1991]. The virtual cathode alytically by Borovsky [1987], and current closure and wave allows only a fraction of electrons to escape the spacecraft; generation for large space structures have been studied in however, some of the escaping electrons may have energies laboratory plasma tanks by Stenzel and Urrutia [1990].…”
Section: Given Our Initial Conditions the Simulations Suggest That Thmentioning
confidence: 99%
“…For dense beams a virtual systems generated in the ambient plasma as a result of large cathode will form in the beam at a point where the beam orbiting structures and large plas•na clouds have therefore electrons stagnate as their velocity away from the spacecraft much in common. The radiation from large space strucis reduced, due to the electrostatic forces in the beam and tures have been studied by Donohue et al [1991], current the spacecraft, which charges to positive potentials [ Winglee closure and radiation for large clouds have been treated anand Pritchett, 1988;Pritchett, 1991]. The virtual cathode alytically by Borovsky [1987], and current closure and wave allows only a fraction of electrons to escape the spacecraft; generation for large space structures have been studied in however, some of the escaping electrons may have energies laboratory plasma tanks by Stenzel and Urrutia [1990].…”
Section: Given Our Initial Conditions the Simulations Suggest That Thmentioning
confidence: 99%
“…This possibility was first investigated by Drell et al [1965] with reference to Alfv6n waves which propagate at frequencies below the ion cyclotron frequency (--•40 Hz). More recent work [Barnett and Olbert, 1986;Hastings et al, 1988;Wang and Hastings, 1991;Donohue et al, 1991] has shown that radiation may also arise in the whistler and Z modes already discussed above.…”
Section: Z Mode Noisementioning
confidence: 97%
“…It was suggested by Estes [1988], Donohue et al [1991], and Sanmartin and Martinez‐Sanchez [1995] that the characteristic lengths of the cloud emitted by an active contactor or the sheath radius on a passive contactor might be larger than the dimensions of the end‐contactor itself; nonlinear effects would adjust contactor areas to an effective value (paper 1) where j th ≡ eN e ( k B T e /2 πm e ) 1/2 is the unperturbed random current density, with T e ≃ 46 eV and the density profile N e in the inner plasmasphere given by .…”
Section: The Radiation Impedance Formulasmentioning
confidence: 99%
“…Pioneer work on the plasma waves radiated by a conductive tether in low Earth orbit (LEO) was carried out by Drell et al [1965]. This work was followed by later authors [ Barnett and Olbert , 1986; Dobrowolny and Veltri , 1986; Hastings and Wang , 1987, 1989; Estes , 1988; Donohue et al , 1991; Sanmartin and Martinez‐Sanchez , 1995] (hereinafter referred to as paper 1) considering the cold plasma approximation. Recently, Biancalani and Pegoraro [2010b] considered radiation by a loop current inside a satellite orbiting in LEO, and Sanchez‐Torres et al [2010] (hereinafter referred to as paper 2) carried out a preliminary study of the Alfvén impedance of a tether in a Juno‐like orbit at the Jovian magnetosphere.…”
Section: Introductionmentioning
confidence: 99%